2007
DOI: 10.1159/000102936
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osteopontin Levels in the Vitreous of Patients with Diabetic Retinopathy

Abstract: Purpose: Osteopontin (OPN) has diverse functions such as cell adhesion, chemoattraction, immunomodulation, and angiogenesis. The aim of this study is to analyze the OPN levels in vitreous fluid obtained from diabetic retinopathy (DR) and non-DR patients. Methods: Nineteen patients out of 11 with DR and 8 without DR underwent pars plana vitrectomy and vitreous fluid was obtained simultaneously. Two distinct sandwich enzyme-linked immunosorbent assay systems (systems 1 and 2) were applied, which have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…However, a significant increase in the level of osteopontin was observed under HG but not normal or osmotic control. This is consistent with the increased levels of osteopontin detected in vitreous of diabetic patients and its association with vascular complications of diabetes (35,62,63).…”
Section: Alterations In Expression Of Ecm Proteins and Their Receptorsupporting
confidence: 88%
See 1 more Smart Citation
“…However, a significant increase in the level of osteopontin was observed under HG but not normal or osmotic control. This is consistent with the increased levels of osteopontin detected in vitreous of diabetic patients and its association with vascular complications of diabetes (35,62,63).…”
Section: Alterations In Expression Of Ecm Proteins and Their Receptorsupporting
confidence: 88%
“…Increased production of fibronectin and its deposition in the basement membrane of retinal vessels during diabetes, and retinal EC under HG conditions, have been previously reported (6,44,47,53,54). The ECM protein osteopontin is a proinflammatory cytokine implicated in the chemoattraction of monocytes and the development of atherosclerosis, as well as vascular complications of diabetes (35,36,46,56). The ␣ v ␤ 3 -integrin is most important for osteopontin prosurvival effects in EC (56).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, osteopontin, a proinflammatory cytokine, was detected in both PDR and control samples, and has diverse functions such as cell adhesion, immunomodulation, and angiogenesis. Vitreous osteopontin levels have been reported to be higher in patients with DR than in normal controls, which suggests that osteopontin plays a role in the pathogenesis of DR [46]. Moreover, angiotensinogen, which is cleaved by renin to form angiotensin I, was detected in the vitreous of PDR and control patients in the present study, and the rennin-angiotensin system (RAS) was suggested to be locally activated in PDR eyes.…”
Section: Pathogenic Implications Of Identified Proteins On Pdrsupporting
confidence: 49%
“…It has been demonstrated that levels of some inflammatory cytokines were significantly higher in the vitreous of patients with proliferative diabetic retinopathy (PDR) than in those of non-diabetic patients (18). This suggests that the inflammatory reaction takes place in the retina during the development of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%